PENGARUH RESEARCH AND DEVELOPMENT (R&D) DAN HUMAN CAPITAL TERHADAP KEMAMPUAN INOVASI PADA USAHA MEBEL DI KABUPATEN MOROWALI - Tovan, Tovan (Katalogis, 2019)
This study aims to determine the simultaneous and partial influence of the ability of research and development (R&D) and human capital on the innovation’s ability in Furniture Business in Morowali. This is quantitative research and the sampling technique applied in this study is purposive sampling with number of sample are 60 respondents with consideration based on the characteristics of respondents namely a minimum operational experience of 1 year and representation of each district. The results of this study indicate that the ability of Research and Development (R&D) and Human Capital Simultaneously and Partially significantly influences the innovation’s ability in Furniture Business in Morowali.